Alteration of Heart Rate Variability in People With Bowel Preparation Before Colonoscopy. Issue 44 (November 2015) - Huang, Shang-Cheng; Fang, Wen-Hui; Wang, Chung-Ching; Chen, Wei-Liang; Kao, Tung-Wei; Hwang, Ling-Ling; Chu, Chi-Ming; Chang, Yaw-Wen
Abstract : Abstract: In current health examination setting, people frequently undergo heart rate variability (HRV) analysis and colonoscopy on the same day. However, it remains unclear whether the bowel preparation before colonoscopy affects HRV. This study aimed to evaluate the association between HRV and bowel preparation. We conducted a cross-sectional observational study of 1755 people from January 2012 to December 2013 in Taipei, Taiwan. The participants, aged 45 to 65 years, received health examinations that included a physical examination, blood tests, and an HRV analysis. Among these people, 1099 additionally received a colonoscopy on the same day and underwent bowel preparation 1 day before the colonoscopy. The association between HRV and bowel preparation was derived by a multivariable linear regression with adjusted confounding factors. Bowel preparation was associated with a lower standard deviation of the normal-to-normal intervals (SDNN), the root mean square of the successive differences (RMSSD), low-frequency power (LF), and high-frequency power (HF) (all P < 0.0001). After adjusting confounding factors, bowel preparation remained correlated with lower SDNN, RMSSD, LF, and HF (all P < 0.0001). Higher serum phosphorus and lower serum potassium levels were noted in the bowel preparation group ( P < 0.0001), and an association between lower HRV and higher serum phosphorus and lower serum potassium levels was only noted in the bowel preparation group. Bowel preparation was significantly associated with lower HRV. The underlying mechanism may be related to an electrolyte imbalance. Cautions may be needed when interpreting HRV reports for people receiving bowel preparations before colonoscopy.